2021
DOI: 10.1094/pdis-09-20-2019-re
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Environment and Vegetable Cropping Systems on Plant-Parasitic Nematode Communities in Southern Georgia

Abstract: Plant-parasitic nematodes (PPN) limit yields in vegetable production in the United States. During the spring and fall cropping seasons of 2018, 436 fields in bare ground and plastic bed cropping systems were randomly sampled from 29 counties in Southern Georgia. The incidence (%), mean and maximum relative abundance (nematodes per 100 cm3 of soil ) of the 10 different PPN genera detected in 32 vegetable crops in bare ground and plastic bed cropping systems include Meloidogyne spp. (67.3, 292, 14144), Nanidorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Meloidogyne spp. were found to be the most important plant parasitic nematodes in vegetable fields in Georgia, USA (Marquez et al, 2021). During the spring and fall cropping periods in 2018, some 436 fields across 29 counties were surveyed and sampled for the incidence and abundance of 10 plant parasitic nematode genera in 32 different vegetable crops.…”
Section: Meloidogyne Sppmentioning
confidence: 99%
“…Meloidogyne spp. were found to be the most important plant parasitic nematodes in vegetable fields in Georgia, USA (Marquez et al, 2021). During the spring and fall cropping periods in 2018, some 436 fields across 29 counties were surveyed and sampled for the incidence and abundance of 10 plant parasitic nematode genera in 32 different vegetable crops.…”
Section: Meloidogyne Sppmentioning
confidence: 99%
“…3,4 Rootknot nematode (RKN; Meloidogyne spp.) is the most serious PPN in vegetable fields in Georgia, 5,6 with M. incognita being the most prevalent RKN species. 7 Important vegetable soilborne fungal pathogens in Georgia include Pythium spp., Fusarium oxysporum, Rhizoctonia solani, Athelia rolfsii, and Sclerotinia sclerotiorium.…”
Section: Introductionmentioning
confidence: 99%
“…A study in corn found no correlation of M. xenoplax densities with EC, pH, or % silt, though densities were correlated to soils with lower organic matter and/or lower clay content (Simon et al., 2018). Similarly, M. xenoplax densities in vegetable crops were not correlated with soil physical or chemical properties (Marquez et al., 2021). As vineyard soils in western Oregon are generally acidic and those in eastern Washington are mostly alkaline, this offers an opportunity to examine the effect of soil texture and pH on reproduction of these two plant‐parasitic nematode species.…”
Section: Introductionmentioning
confidence: 99%